Implikasi Teori Belajar dalam Pembelajaran Mahasiswa Bimbingan dan Penyuluhan Islam - Fiqri Permana; Atikah Asna (Jurnal Budi Pekerti Agama Islam, 2025)
This study aims to analyze the implications of learning theories in the learning process of students of the Islamic Guidance and Counseling study program. Learning theories such as behaviorism, cognitivism, constructivism, and humanism provide different but complementary frameworks in supporting the formation of student competencies. The results of the study indicate that the application of learning theories appropriately can increase the effectiveness of learning through integrated methods, such as case-based discussions, counseling simulations, and spiritual reflection. This study recommends the development of a curriculum that is more adaptive to student needs and a pedagogical approach that combines Islamic values ​​with modern learning theories. Thus, students are able to internalize Islamic values ​​while applying practical skills in guidance and counseling.